(untitled) (Sains Humanika, 2021)
As business world becomes more competitive, the person’s ability to work individually and in team become the important factor to win the competition. In addition, the effects of globalization have raised company awareness of the importance of multicultural teams in gaining a global competitive advantage. Therefore, it becomes one of universities’ role to prepare the students with ability to work in multicultural team. This research want to compare the cultural intelligence (CQ) and students’ attitude towards teamwork between Indonesian and Australian students with Institut Teknologi bandung and Griffith University students as respondents. The result showed that there is significant difference between Australian and Indonesian students for CQ and attitude towards teamwork where for CQ Indonesian students showed higher mean for both CQ and attitude towards team work..